Kanabidiol (CBD) in koža - Tavčar, Eva (Farmacevtski vestnik, 2023)
Cannabidiol (CBD) is a very interesting ingredient both in the world of dermatological research and cosmetic science. Dermal medicines with CBD as an active ingredient with marketing authorisation are not yet in use. However, the European Commission has approved CBD as a cosmetic ingredient with anti-sebum, antioxidant, skin-protecting and skin-conditioning effects. In the human body, CBD is active in the endocannabinoid system, which is responsible for maintaining the balance between cells and their environment. In the endocannabinoid system of the skin, it acts on endocannabinoid receptors and by other mechanisms, by which the cells maintain homeostasis. In medicinal research, CBD is being researched in the treatment of atopic skin, psoriasis, acne, skin tumours and in the healing of wounds. Within the scope of the article, we focused primarily on independent research on the effects of CBD on the skin.
Keywords: akne; atopijska koža; dermatiki; kanabidiol (CBD); Luskavica; Mozoljavost; vnetje